(untitled) (Interdisciplinary Studies Journal, 2021)
The objective of this article is to analyze how the campaign "16 Days of Activism to End Violence Against Women" was implemented in the municipality of Taquara, located in the state of Rio Grande do Sul, Brazil. The analysis focuses on the international campaign and the importance of the debate on gender-based violence. The methodology used was descriptive, based on bibliographic sources and data collection from the official page of the international campaign, the content of the municipal campaign’s Facebook page, and local media outlets. The results show that the dynamics employed in the municipality were in line with the original global objectives: a diversity of actors involved, flexibility in organizing actions (government and civil society), with the main outcome being the creation of municipal law No. 6187/2019.